Isomers and their metabolites of endosulfan induced cytotoxicity and oxidative damage in SH‐SY5Y cells. Issue 4 (31st October 2014) - Enhui, Zhu; Na, Chen; MengYun, Liu; Jia, Li; Dan, Li; Yongsheng, Yang; Ying, Zhang; DeFu, He
ABSTRACT: As an organochlorine insecticide, endosulfan has been widely banned or restricted, but it is still largely used in many developing countries. Previous studies have shown multiple adverse health effects of endosulfan. However, the neurotoxicity of endosulfan has not been fully elucidated. In this study, endosulfan isomers (α‐/β‐endosulfan) and their major metabolites (endosulfan sulfate, endosulfan diol, and endosulfan lactone) were, respectively, exposed to human neuroblastoma SH‐SY5Y cells. Results showed that both α‐endosulfan and β‐endosulfan caused decrease of cell viability and morphological damages in a dose‐dependent manner. Their median effective concentrations (EC50s ) were respectively 79.6 μM (α‐endosulfan) and 50.37 μM (β‐endosulfan) for 72 h exposure. EC50s of α/β‐endosulfan mixture were lower than that of the single isomer. However, EC50s of its metabolites were higher than that of technical endosulfan. Endosulfan and its metabolites caused increases of reactive oxygen species and the lipid peroxidation, but decrease of superoxide dismutase in a dose‐dependent manner. These results indicate that α‐endosulfan exhibits higher neurotoxicity than β‐endosulfan. Mixture of endosulfan isomers shows stronger cytotoxicity than the single isomer. After endosulfan is degraded, cytotoxicity of its metabolites decreases gradually. The neurotoxicity of endosulfan and its metabolites is closely related to oxidative damage and antioxidative deficit. © 2014 Wiley Periodicals, Inc. Environ Toxicol 31: 496–504, 2016.